Screening for germline BRCA1, BRCA2, TP53 and CHEK2 mutations in families at-risk for hereditary breast cancer identified in a population-based study from Southern Brazil - Palmero,Edenir Inêz (2016)
Abstract In Brazil, breast cancer is a public health care problem due to its high incidence and mortality rates. In this study, we investigated the prevalence of hereditary breast cancer syndromes (HBCS) in a population-based cohort in Brazils southernmost capital, Porto Alegre. All participants answered a questionnaire about family history (FH) of breast, ovarian and colorectal cancer and those with a positive FH were invited for genetic cancer risk assessment (GCRA). If pedigree analysis was suggestive of HBCS, genetic testing of the BRCA1, BRCA2, TP53, and CHEK2 genes was offered. Of 902 women submitted to GCRA, 214 had pedigrees suggestive of HBCS. Fifty of them underwent genetic testing: 18 and 40 for BRCA1/BRCA2 and TP53 mutation screening, respectively, and 7 for CHEK2 1100delC testing. A deleterious BRCA2 mutation was identified in one of the HBOC probands and the CHEK2 1100delC mutation occurred in one of the HBCC families. No deleterious germline alterations were identified in BRCA1 or TP53. Although strict inclusion criteria and a comprehensive testing approach were used, the suspected genetic risk in these families remains unexplained. Further studies in a larger cohort are necessary to better understand the genetic component of hereditary breast cancer in Southern Brazil.